Classification of Death Causes after Transplantation (CLASS): Evaluation of Methodology and Initial Results. (4th October 2017) - Wareham, Neval Ete; Da Cunha-Bang, Caspar; Borges, Álvaro H; Ekenberg, Christina; Gerstoft, Jan; Gustafsson, Finn; Hansen, Ditte; Helleberg, Marie; Heilmann, Carsten; Hillingsø, Jens; Krohn, Paul Suno; Lodding, Isabelle Paula; et al.
Abstract: Background: Correct classification of underlying causes of death is an important outcome among transplant recipients. Deaths due to infections and adverse graft function are often misclassified. We aimed to develop and validate a system to code causes of death in hematopoietic stem cell (HSCT) and solid organ (SOT) transplant recipients and to identify characteristics that could identify deaths with a clear cause. Methods: A standardized case record form (CRF) was used to collect clinical information from consecutive recipients transplanted at a transplant hospital between 2004 and 2014, who died 2010–2013 (derivation cohort). Causes of death were determined through a centralized process involving two medical experts who independently assessed each CRF. Factors associated with independent agreement between reviewers were assessed and validated on patients who died 2013–2016 (validation cohort). All cases without agreement were adjudicated. Death causes ascertained by our system were compared with death causes in the Danish National Death Registry. Results: 388 transplant recipients died during 2010 to 2016 (196 (51%) SOT and 192 (49%) HSCT). Using our methodology, leading underlying causes of death among SOT and HSCT were classified as cancer (20%, 48%), graft rejection/failure/graft-vs.-host-disease (35%, 28%) and infections (20%, 11%) (Figure 1). Death causes were in agreement with the Danish registry in only 37% of cases in derivation cohort. In the derivation cohort, kappa was 0.64 (95% CI 0.56–0.69) for independent agreement between the two experts (all remaining classified upon adjudication) (Figure 2). Odds for independent agreement were higher in cases with a history of cancer (aOR 3.20 (1.45–7.06)); among 174 with this characteristics, kappa was 0.71 (0.64–0.79). These findings were reproducible in the validation cohort (kappa for overall independent agreement=0.63 (0.52 – 0.73); among 54 recipients with a history of cancer, kappa = 0.71 (0.57–0.84)). Conclusion: We developed and validated a method able to systematically and reliably classify underlying cause of death among transplant recipients. There was a high degree of discordance between this classification and that in the National Death Registry. Our method can be applied to any cohort. Disclosures: All authors: No reported disclosures.